2019
DOI: 10.1177/2332858419872212
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Open Textbook Adoption on Learning Performance and Course Withdrawal Rates: A Meta-Analysis

Abstract: Open textbooks have been developed in response to rising commercial textbook costs and copyright constraints. Numerous studies have been conducted to examine open textbooks with varied findings. The purpose of this study is to meta-analyze the findings of studies of postsecondary students comparing learning performance and course withdrawal rates between open and commercial textbooks. Based on a systematic search of research findings, there were no differences in learning efficacy between open textbooks and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 69 publications
(94 reference statements)
7
68
0
Order By: Relevance
“…However, there were no statistically significant differences between textbooks in student perceptions of items relating to everyday life examples and difficulty. The lack of difference in learning performance by textbook type is consistent with previous quasi-experimental research comparing open textbooks with commercial textbooks (e.g., Hendricks et al, 2017;Clinton, 2018;Jhangiani et al, 2018;Lawrence and Lester, 2018;see Hilton, 2016, for a systematic review; see Clinton and Khan, 2019, for a meta-analysis). However, a key difference is that in this experiment, it was certain that everyone had access to the excerpt of the textbook.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, there were no statistically significant differences between textbooks in student perceptions of items relating to everyday life examples and difficulty. The lack of difference in learning performance by textbook type is consistent with previous quasi-experimental research comparing open textbooks with commercial textbooks (e.g., Hendricks et al, 2017;Clinton, 2018;Jhangiani et al, 2018;Lawrence and Lester, 2018;see Hilton, 2016, for a systematic review; see Clinton and Khan, 2019, for a meta-analysis). However, a key difference is that in this experiment, it was certain that everyone had access to the excerpt of the textbook.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, when expanding comparisons to students at different institutions, at least one study has noted poorer learning performance for students in courses using open textbooks (Gurung, 2017). Systematic reviews and a meta-analysis have concluded that, based on the overarching findings across studies, the learning outcomes from open and commercial textbooks are similar (see Hilton, 2016Hilton, , 2019Clinton and Khan, 2019, for a meta-analysis). However, these findings regarding the efficacy of open textbooks are confounded in several ways.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although OER exhibit positive potential related to textbook affordability and academic achievement, few studies have explored that potential among historically underserved students (Clinton & Khan 2019;Gurung 2017). Due to increasingly high textbook prices, it is believed that OER can reach socially excluded students (Lane 2013), increase participation among underrepresented groups (Bossu, Bull, & Brown 2012), and bridge the gap between formal and informal education (Meiszner 2011).…”
Section: Textbook Affordability Among Historically Underserved Studentsmentioning
confidence: 99%
“…Despite OER's ability to reduce current price barriers to higher education (Hodgkinson-Williams & Arinto 2017), very little research to date has explored OER's specific impact among those who are presumed to benefit most from that potential: historically underserved student populations (see Arbor 2011;Jenkins et al 2018;Clinton & Khan 2019;Colvard, Watson, & Park 2018;Delgado, Delgado, & Hilton 2019). This is because OER and textbook affordability studies typically control for issues of difference, or else fail to disaggregate their final data altogether.…”
mentioning
confidence: 99%